The Gender Composition of Corporate Boards and Firm Performance: Evidence from Russia - Tatiana Garanina; Alexander Muravyev (Institute of Labor Economics (IZA), 2019)
This paper studies economic effects of the gender composition of corporate boards, employing a new and unique longitudinal dataset of virtually all Russian companies whose shares were traded on the national stock market between 1998 and 2014. Using multiple identification approaches, alternative measures of gender diversity, and several performance indicators, we find some evidence that companies with gender-diverse boards have higher market values and better profitability. These effects are particularly pronounced when firms appoint several women directors, which is consistent with the critical mass theory. The effects appear to be stronger in bad economic times or for firms experiencing economic difficulties. Overall, the Russian data lend some support to "the business case" for more women on corporate boards.
Keywords: G34; J16; 330; board of directors; gender diversity; firm performance; Russia